The (Political) Forms of Technology: Antonioni, Olmi, De Seta, and Post-World War II Industrial Cinema. (4th May 2019) - Antonello, Pierpaolo
ABSTRACT: This essay examines three exemplar cases of Italian industrial cinema, a genre that experienced a particular and extended apogee during the decades of Italy's economic boom: Michelangelo Antonioni's Sette canne, un vestito (1948), Ermanno Olmi's Costruzioni meccaniche Riva (1956), and Vittorio De Seta and Franco Dodi's Gela 1959: pozzi a mare (1960). Aims of this analysis are to tease out some ideological and aesthetic tensions that could appear to point, on the one hand, to some formal and thematic continuity between pre-World War II output and that of later years; and, on the other, to the particular role played by technology in shaping a specific formalistic vocabulary in these films.